Geoenvironmental engineering contaminated ground : fate of pollutants and remediation - Yong, R. N.; Thomas, H. R. (Thomas Telford, 1997)
Contains the proceedings of the British Geotechnical Society's conference for geo-environmental engineering of contaminated land. This work encompasses the issues of pollution to the ground, from the impact of past and current industrial activities, to the need for disposal of waste generated by society in landfill sites.